PENDIDIKAN KARAKTER KEWIRAUSAHAAN: STUDI NILAI SPIRITUAL ISLAM BERDASARKAN TAFSIR TARBAWI QS. ALI IMRON : 200 - Irfan Afandi (Fakultas Tarbiyah, Universitas Ibrahimy, 2022)
The world, lately, has experienced various challenges, both from technological developments, disasters and pandemic diseases. However, human life must continue to run as it should with various creative efforts. For the purpose of creating creative entrepreneurship, character education is needed. One of them is sourced in Qs. Ali Imron: 200 where this verse teaches four spiritual values namely patience level 1 & 2, ribath and taqwa. This spiritual value can be taught with a pattern of character education with an integrative learning model. This allows the delivery of four spiritual values contained in the verse. Integrative learning patterns that can be applied include the first, interdisciplinary patterns in which learning how to integrate a concept of skills or abilities that are grown and developed in one subject or sub-topic in one field of study; second, interdisciplinary learning where learning is carried out by combining fields of study by finding the same concepts, skills, and attitudes as the four moral values.